Orbital- and millennial-scale Antarctic Circumpolar Current variability in Drake Passage over the past 140,000 years - Wu, Shuzhuang (Nat Commun, 2021)
The Antarctic Circumpolar Current (ACC) plays a crucial role in global ocean circulation by fostering deep-water upwelling and formation of new water masses. On geological time-scales, ACC variations are poorly constrained beyond the last glacial. Here, we reconstruct changes in ACC strength in the central Drake Passage in vicinity of the modern Polar Front over a complete glacial-interglacial cycle (i.e., the past 140,000 years), based on sediment grain-size and geochemical characteristics. We found significant glacial-interglacial changes of ACC flow speed, with weakened current strength during glacials and a stronger circulation in interglacials. Superimposed on these orbital-scale changes are high-amplitude millennial-scale fluctuations, with ACC strength maxima correlating with diatom-based Antarctic winter sea-ice minima, particularly during full glacial conditions. We infer that the ACC is closely linked to Southern Hemisphere millennial-scale climate oscillations, amplified through Antarctic sea ice extent changes. These strong ACC variations modulated Pacific-Atlantic water exchange via the “cold water route” and potentially affected the Atlantic Meridional Overturning Circulation and marine carbon storage.